A contract in transition: online press and its audience - Raimondo Anselmino, Natalia (2014)
For quite a few years, it has been announced (Igarza, 2011; Jenkins, 2008; Jenkins and Deuze, 2008) that we are at a transition period, in which a new media ecology is been built, more hybrid than the previous ones, for several reasons that, in a way, are dealt with in the different chapters of this book. In this sense, the Latin American media system is not an exception.